Time to Occurrence of Phlebitis After Continuous Infusion of Total Nutrient Admixture Through Peripheral Veins: An Experimental Animal Study - Guo JL; Yan XY; Zhao QL; Gao CN; Wei CH; Wei Z; Yue YT; Guo XJ (Dove Medical Press, 2022)
Jin-Li Guo,1,* Xian-Yan Yan,1,* Qing-Li Zhao,1 Chao-Na Gao,1 Chen-Hui Wei,1 Zhuan Wei,1 Yi-Ting Yue,2 Xiu-Juan Guo1 1Department of Nursing, Second Hospital of Shanxi Medical University, Taiyuan, People's Republic of China; 2Department of Nursing, Fenyang College of Shanxi Medical University, Fenyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Jin-Li GuoDepartment of Nursing, Second Hospital of Shanxi Medical University, No. 382 of Wuyi Road, Xinghualing District, Taiyuan, 030001, People's Republic of ChinaTel +86 13546395590Email guojl_551@163.comObjective: To study the limit time of phlebitis caused by continuous infusion of KabivenTM Pl and TNA (KabivenTM Pl+ alanyl glutamine + potassium aspartate) through a peripheral vein, and to provide a reference for clinical formulation of preventive measures for phlebitis.Methods: White rabbits (n = 72) were randomly divided into three groups: group A (Normal saline), group B (Kabiven™ Pl), and group C (TNA). Blood was collected from the ear margin vein before administration and after three hours, four hours, five hours, and six hours of administration. CRP and TNF-ɑ were measured by enzyme-linked immunosorbent assay. Hematoxylin and eosin staining and immunohistochemical staining were performed on tissue samples taken from the insertion point of the indwelling needle, the tip of the indwelling needle, and 1 cm from the tip of the indwelling needle, closer to the heart, to analyze early pathological changes in blood vessels.Results: (1) There were no visible inflammatory symptoms in groups A, B, or C within 6 hours. (2) Four hours after starting intravenous administration, the levels of inflammatory markers in groups B and C were higher than in group A, and (3) the degree of inflammatory cell infiltration in groups B and C was more severe than in group A. (4) In all groups, the inflammatory reaction at the tip of the indwelling needle was more severe than at the other two sites.Conclusion: When the emulsions TNA and Kabiven™ Pl are infused through a peripheral vein, (1) four hours may be considered as the maximum time for continuous intravenous infusion in the same vein before inflammatory changes become evident, and (2) systematic assessment of the tip of the indwelling needle should be considered for inclusion in the nursing plan for phlebitis monitorings.Keywords: peripheral vein, Kabiven™ Pl, TNA, phlebitis, limit time, CRP, TNF-&#x0251